Standing on the shoulders of giants or science? Lessons from ordoliberalism - Lars P. Feld; Ekkehard A. Köhler (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2023)
James Buchanan would have celebrated his 100th birthday in 2019. This serves as an inspiration to look at the future of public choice and the question of how much normativity public choice can bear. In our analysis we draw parallels between public choice and German ordoliberalism (and its source in the Freiburg School of Economics). We argue that the reception of ordoliberalism exemplifies easy-to-grasp pitfalls that should be taken seriously. We anchor the future agenda of public choice in a solid individualist perspective. Similar to ordoliberalism, public choice will have to clarify its relation to normative economics. The effects of rules and institutions and their working properties should be thoroughly analyzed empirically. The role of ideas is important for the normative foundation of both public choice/ constitutional economics and ordoliberalism, and is rooted in normative individualism. It provides a benchmark by which rules and institutions can be judged as favorable.
Keywords: B13; B26; B31; D78; E61; E63; 330; Public Choice; Methodology; James Buchanan; Normativity; Individualism